Milestones of Da’wa in the Stories of Prophets in the Light of the Holy Qur’an - The Story of the Prophets of Allah Adam and Noah, peace be upon them, (Analytical Study) - Al- Faqih, Abdulrahman Qaid Abdulrahman (Journal of Islamic Sciences, 2020)
The study aimed to identify the features of the call in the stories of the prophets in the light of the Holy Qur’an i.e. the story of the Prophets of Allah, Adam and Noah, peace be upon them as a model. The descriptive approach was used. The study included three parts, the first part addressed the definition of the call linguistically and conventionally. The second part addressed the features of the call in the story of the Prophet of God, Adam, peace be upon him. The third part addressed the features of the call in the story of the Prophet of God, Noah, peace be upon him. This study concluded the flowing results (1) every messenger whose story was mentioned in the Holy Qur’an was characterized by the communication of the revelation of Allah, and the fact that no one was forced to enter into religion. Such important features are among the most important concepts of common teaching among all the prophets; (2) perseverance, patience and endurance in the path of call are vital in the success of the message of the prophets.
Keywords: milestones; Da’wa; stories; prophets; Adam; Noh